Monitoring of Harmful Algal Blooms - Pettersson, Lasse H.; Pozdnyakov, Dmitry; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Sometimes known as "Red Tides", some of the wide variety of phytoplankton species in the World$1 (Bs oceans produce toxins which can harm marine life. In certain circumstances, these harmful algal blooms can even cause illness or death in humans. Shellfish filter feed on phytoplankton and concentrate their toxins in their bodies and people who eat them can contract life threatening food poisoning. A number of countries have monitoring programmes to measure the presence of toxins in algal blooms. Monitoring of Harmful Algal Blooms is all about the research techniques to monitor visible algal blooms and through remote sensing, including infrared techniques, predict them through mathematical modelling.s
Aspects of Harmful Algal Blooms (HAB) -- Biology and ecology of some harmful algal species (focus on Chantonella-tbd) -- Retrieval of algal bloom related quantities from space -- Monitoring algal bloom from space -- Integrated approach for operational and forecasting HAB events.
Keywords: Environmental sciences; Life sciences; Geochemistry; Oceanography; Geographical information systems; Ecology; Environmental toxicology; Environment; Ecotoxicology; Biogeosciences; Geochemistry; Oceanography; Geographical Information Systems/Cartography.; Ecology